Post-Thaw Quality of Bali Cattle Semen in CEP Diluent: Optimizing Temperature and Duration - Amalia, Farah Nurinda; Nur Ducha; Qomariyah, Nur; Fardha Ad Durrun Nafis (ANIMAL PRODUCTION, 2025)
The thawing method is a crucial stage in the semen freezing process because it determines the quality of spermatozoa post-thawing. This study aims to evaluate the effect of thawing temperature and duration on the quality of frozen Bali cattle semen in CEP diluent. Semen was collected from a Bali bull at the Singosari Artificial Insemination Center, added to CEP diluent, and frozen. It was then thawed using three temperature variations (37°C, 30°C, and 25°C) and two durations (30 and 60 seconds) in a 3x2 factorial completely randomized design. Post-thawing evaluation included motility, viability, and membrane integrity analyzed using two-way ANOVA and Duncan's test. The results showed that thawing temperature significantly affected all parameters (P<0.05). A temperature of 37°C produced the highest motility, viability, and membrane integrity. Thawing duration significantly affected motility and membrane integrity, with the best results obtained at 30 seconds. There was no significant interaction between thawing temperature and duration, but the combination of 37°C and 30 seconds produced the best post-thawing motility (56.67±2.89). An optimal thawing combination was identified, with temperature and duration independently affecting sperm quality, offering practical guidelines for Bali cattle artificial insemination programs.